Pengaruh Tingkat Inflasi, Tigkat Bunga Deposito Dan Kurs Valuta Asing terhadap Capital Gain / Loss Pada Perusahaan Real Estate dan Property Di Bursa Efek Indonesia - Febri Irwansyah; Zulbahridar '; Rahmiati Idroes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Aims to determine the effect of the inflation rate, interest rate and foreign exchange deposite to the capital gain / loss on real estate companies and property at Indonesian Stock Exchange.The research was conducted on the real estate and property compenies in 2009 – 2012 using the methode of purposive sample. Obtained a sample of 16 companies. Data analys using multiple linear regression. Based on the result on this study concluded that the variable inflation rates, deposite interest rates, foreign exchange rates partially significant effect on the capital gain / loss.Keywords : Inflation ratesdeposite interest rates, foreign exchange, Capital Gain / Loss